Antagonism toward African immigrants in Johannesburg, South Africa : an Integrated Threat Theory (ITT) approach. - Laher, Hawabibi (My University, 2009)
South Africa and Johannesburg are rapidly becoming global entities in the worldwide domain. The history of South Africa embodies a place of segregation and discrimination. At present, South Africa is characterised as a place of promise for the future. As a result, South Africa (specifically Johannesburg), “has become a magnet for people from other provinces, the African continent, and indeed, the four corners of the world” (Masondo, 2004). Yet these movements are not always met with a positive response. This study sought to investigate whether the Integrated Threat Theory (ITT) of prejudice (Stephan & Stephan, 1996) explains prejudice and social distance towards African immigrants in South Africa. The theory suggests that the factors, inter-group anxiety, realistic threats, symbolic threats and negative stereotypes, affect prejudice. Nature of communication was also used as a predictor of prejudice. The sample consisted of 345 South African citizens. A questionnaire was issued to the participants in order to establish how they feel (perception) or have felt, interacting with immigrants from African countries. Various scales were used to ascertain this information. Multiple linear regression and path analyses were conducted. Findings indicated that intergroup anxiety, symbolic threats, realistic threats and stereotypes as well as the nature of communication predicted prejudice to a large extent (68% of the variance explained) and predicted social distance to a moderate extent (42% of the variance explained).
Keywords: Antagonism; Immigrants; Integrated Threat Theory; South Africa